Refleksje o edukacji w dobie przemian globalizacyjnych - Myszka, Lucyna (Kultura-Społeczeństwo-Edukacja, 2015)
As a consequence of globalization human life is subjected to many mechanisms that go along with it for example homogenization, culture diffusion, consumptionism, relativism and constant change, which lead to unreflectiveness affecting all aspects of human life. A human beeing exists in a common reality in accordance to a very flexible scenario, without much thought about the sense of existence. This situation reflects on education, which should concentrate on efficent spreading of knowledge and skills necessary to live in current conditions, which are a source of many chances but also dangers. Those changes can’t be analyzed without taking markets into consideration, understood as having and usefulness. Those trends cause the „production” of alumni that are very efficient from an economical point of view and oriented on self realization, but aren’t oriented on reflective exploration of the world. This situation results in comparing humans to machines and in an obsessive want of getting a diploma which certifies obtaining education understood as a commodity. This in turn is an incentive to reflect upon the foundations of education a process that is the most important investment in the development of human capital.